Survival in Patients With Nonischemic Cardiomyopathy With Preserved vs Reduced Ejection Fraction - Nancy Luo, MD, MHS (Elsevier, 2021)
Background: Prior studies suggest similar long-term mortality rates for patients with heart failure (HF) with preserved ejection fraction (HFpEF) vs reduced ejection fraction. However, although coronary heart disease (CHD) is associated with worse prognosis in HF, clinical outcomes are less well characterized for HF without CHD. We investigated the characteristics and 5-year mortality outcomes among patients with HF without significant CHD, stratified by EF. Methods: Patients with clinical heart failure who underwent coronary angiography at Duke University Medical Center from 1996 through 2009 and had no significant CHD with EF ≤ 40% were compared with patients without significant CHD with EF > 40%. Survival was examined using Kaplan-Meier methods and multivariable Cox proportional hazards modeling. Analyses were repeated using EF ≥ 50%. Results: Of 3154 patients with HF without significant CHD, 1530 (48.5%) had HFpEF (EF > 40%). These patients were older and more likely to have a Charlson Index ≥ 2 than patients with reduced EF. Patients with HFpEF had a lower risk of death than those with reduced EF (unadjusted hazard ratio [HR] 0.85; 95% confidence interval [CI] 0.74-0.99). From 1996 through 2009, the secular trend of death decreased among patients without CHD and with reduced EF (HR 0.92; 95% CI 0.88-0.97) but not among those with preserved EF (HR 0.99; 95% CI 0.93-1.05; P interaction 0.095). No finding was significant after multivariable risk adjustment. Results were consistent when defining preserved EF as EF ≥ 50%. Conclusions: Among patients without significant CHD, those with HFpEF had similar risks of 5-year mortality as patients with HF with reduced ejection fraction. Résumé: Introduction: Des études antérieures indiquent des taux de mortalité à long terme similaires entre les patients atteints d’insuffisance cardiaque (IC) avec fraction d’éjection (FE) préservée (ICFEP) vs les patients atteints d’IC avec FE réduite (ICFER). Toutefois, bien que la coronaropathie soit associée à un plus mauvais pronostic de l’IC, les résultats cliniques sont moins bien définis que ceux de l’IC sans coronaropathie. Nous avons examiné les caractéristiques et les résultats des patients atteints d’IC sans coronaropathie importante, stratifiés selon la FE, sur la mortalité dans les cinq ans. Méthodes: Nous avons comparé les patients montrant des signes cliniques d’IC qui avaient subi une angiographie coronarienne à la Duke University de 1996 à 2009 et n’avait pas de coronaropathie importante avec FE ≤ 40 % aux patients sans coronaropathie importante avec FE > 40 %. Nous avons examiné la survie à l’aide de la méthode de Kaplan-Meier et du modèle multivarié à risques proportionnels de Cox. Nous avons répété les analyses en fonction d’une FE ≥ 50 %. Résultats: Parmi les 3 154 patients atteints d’IC sans coronaropathie importante, 1 530 (48,5 %) avaient une ICFEP (FE > 40 %). Ces patients étaient plus âgés et plus susceptibles d’avoir un indice de Charlson ≥ 2 que les patients atteints d’ICFER. Les patients atteints d’ICFEP avaient un risque plus faible de mortalité que ceux atteints d’une ICFER (rapport de risque [RR] non ajusté 0,85; intervalle de confiance [IC] à 95 % 0,74-0,99). De 1996 à 2009, la tendance séculaire de la mortalité avait diminué chez les patients sans coronaropathie et qui avaient une FE réduite (RR 0,92; IC à 95 % 0,88-0,97), mais non chez ceux qui avaient une FE préservée (RR 0,99; IC à 95 % 0,93-1,05; valeur P de l’interaction 0,095). Aucun résultat n’était significatif après l’ajustement multivarié en fonction du risque. Les résultats étaient cohérents lorsque la FE préservée était définie par une FE ≥ 50 %. Conclusions: Chez les patients sans coronaropathie importante, ceux atteints d’une ICFEP avaient des risques similaires de mortalité dans les cinq ans aux patients atteints d’ICFER.